(untitled) (The Review of Diabetic Studies, 2025)
Healthcare-associated infections (HAIs) remain a major challenge to patient safety, healthcare quality, and system sustainability worldwide. Despite the availability of evidence-based infection prevention and control (IPC) guidelines, fragmented implementation across healthcare disciplines continues to limit their effectiveness. This comprehensive review aims to examine how multidisciplinary collaboration, supported by digital health solutions, can enhance IPC outcomes across healthcare settings. The review synthesizes evidence from medical, nursing, laboratory, pharmacy, allied health, environmental, and administrative domains, highlighting their complementary roles in preventing infection transmission. In addition, the review explores the growing contribution of digital health technologies, including electronic health records, surveillance systems, artificial intelligence, and telemedicine, in strengthening IPC compliance, early detection, and data-driven decision-making. Findings indicate that integrated, team-based IPC approaches improve adherence to preventive measures, reduce infection rates, and enhance organizational resilience, particularly when supported by robust digital infrastructure and leadership commitment. The review concludes that sustainable improvement in infection prevention requires a systems-based model that aligns multidisciplinary teamwork with digital innovation, governance, and continuous quality improvement. Future efforts should focus on scalable, interoperable, and workforce-centered IPC strategies to address emerging infectious threats and evolving healthcare demands.